2019
DOI: 10.1371/journal.pone.0226153
|View full text |Cite
|
Sign up to set email alerts
|

Fiber visualization for preoperative glioma assessment: Tractography versus local connectivity mapping

Abstract: In diffusion MRI, the advent of high angular resolution diffusion imaging (HARDI) and HARDI with compressed sensing (HARDI+CS) has led to clinically practical signal acquisition techniques which allow for the assessment of white matter architecture in routine patient studies. However, the reconstruction and visualization of fiber pathways by tractography has not yet been established as a standard methodology which can easily be applied. This is due to various algorithmic problems, such as a lack of robustness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Tractography is a technique to measure the strength of the white matter (WM) connection by tracking the fiber pathway connecting different brain regions. However, directly performing tractography on the brain with a tumor may cause tracking failure or artifacts, e.g., an unrealistic belt of fibers surrounding the tumor 24 . To bypass the need to perform tractography on the lesioned brain, previous studies proposed to generate a template from healthy controls for tract localization, and the strength of WM connection was then robustly estimated by comparing patients to healthy controls 25, 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tractography is a technique to measure the strength of the white matter (WM) connection by tracking the fiber pathway connecting different brain regions. However, directly performing tractography on the brain with a tumor may cause tracking failure or artifacts, e.g., an unrealistic belt of fibers surrounding the tumor 24 . To bypass the need to perform tractography on the lesioned brain, previous studies proposed to generate a template from healthy controls for tract localization, and the strength of WM connection was then robustly estimated by comparing patients to healthy controls 25, 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Directly performing tractography in the lesioned brain may cause artefacts, e.g., an unrealistic belt of fibers surrounding the tumor core. (27),(28) Previous evidence shows that the white matter integrity in glioma patients can be quantitatively assessed using the fractional anisotropy (FA), a robust measure derived from dMRI, after applying the deformable nonlinear registration (2931). Further studies showed that the tract integrity of the lesioned brain can be estimated by using the tract templates derived from healthy controls (3234), and the alignment-invariant tract representation (FA skeleton) generated using the tract-based spatial statistics (TBSS) (35).…”
Section: Methodsmentioning
confidence: 99%
“…Amongst these methods, constrained spherical deconvolution (CSD) (25) has been shown to improve the assessment of complex, intra-voxel fiber configuration significantly. Thus, fiber-tracking procedures based on advanced DWI methods allow a more accurate estimation of complex fiber architectures (7) and are increasingly used for planning the extent of resection in brain tumors adjacent to eloquent areas (23,(26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative white matter (WM) fibers visualization and quantitative assessment of tissue organization in patients with brain pathology can assist in the selection of surgical approach and setting maximum boundaries for the extent of lesion resection while preserving function. 1 3 …”
Section: Introductionmentioning
confidence: 99%